PENGEMBANGAN DIRI GURU DALAM MEMBANGUN ORIENTASI KEPALA SEKOLAH KE MASA DEPAN (Studi Kasus di Sekolah Menengah Negeri 9 Muaro Jambi) - Mukhtar Mukhtar; Muhajirin; Kasful Anwar; Asrulla (Jurnal Genta Mulia, 2024)
The development of the ability to build future school leadership orientation is necessary, as this educational system must be in line with the relevance of needs and demands of the times. This is exemplified by the head of SMPN 9 Muaro Jambi by developing the teachers themselves according to their needs and demands. This qualitative research focuses on the subject of the study, which is the head of the school, deputy head, and teachers. Data collection was done through observation, interviews, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data display, and data conclusion. The results of the study show that the development of teachers conducted by the head of SMPN 9 Muaro Jambi is done independently and professionally, with strong management skills, decision-making abilities, and potential for improving teacher quality. The development of teachers is carried out through participation in activities such as the Musyavarah Guru Mata Pelajaran (M(CMP) Kabupaten), becoming a Guru Penggerak or Pengair Praktek (PP), attending training on teaching platforms (PMM), forming learning communities in schools (KOMBHL), and participating in the local facilitation program (FASDA) conducted by the Tanoto Foundation.